Spectroscopic Determination of Riboflavin in Formulations - Felice Choragudi, Shechinah; Santoshi, K.; Santhi, G.; Keerthana, V.; Ravali, V.; Swetha Parvathi, S. (Asian Journal of Chemistry, 2010)
Two simple, sensitive and reproducible spectroscopic methods are developed for the determination of riboflavin in pharmaceutical formulations. Method A is based on formation of ion association complex between riboflavin and bromothymol blue to produce a bluish green coloured species with lmax 440 nm and its absorbance is linear with concentration over the range of 40-200 μg/100 mL. Method B is based on a similar principle involving treatment of riboflavin with congo red to produce a pale yellow coloured species that shows maximum absorption at 430 nm and exhibits linerarity in the concentration range of 40-200 μg/100 mL. Results of analysis were validated statistically and by recovery studies. This method could be successfully employed for routine determi-nation of riboflavin in formulations